PERSEPSI AKAD JUAL BELI (AL-BAI’) DI KALANAN GENERASI MILENIAL SESUAI DENGAN SYARIAT ETIKA BISNIS ISLAM - Saputri, Nelsa Ummi; Fasa, Muhammad Iqbal; Suharto, Suharto (Jurnal Ilmiah Pendidikan dan Keislaman, 2021)
Buying and selling is a transaction made by humans in order to meet their needs, by selling goods or services between two people and more. In this study has the goal to find out how the perception of buying agreements among millennials, whether it is in accordance with the principles of Islamic business ethics. Therefore, it is expected that in the future the results of writing this paper can be used as a reference model for millennials in transacting buying and selling. This research is done in a descriptive way that uses library studies and summarizes the results of research that has been done before. In carrying out buying and selling agreements, business people have been able to understand and apply the pillars and conditions that have been determined by being sourced in the Qur'an and Hadith